Specifics of Information Risks in the Municipal Administration System of Modern Russia - BALYNSKAYA, Natalya Rinatovna; KOPTYAKOVA, Svetlana Vladimirovna (Journal of Advanced Research in Law and Economics, 2016)
This article deals with the problems of information support of municipal administration system in Russia. The municipal level of government is the closest to the people: here all political initiatives of citizens are implemented at the first stage. That is why the municipal level is so exposed to risks in the distribution of information. The article analyzes the specifics of information risks in the municipal administration system. The information on the ‘input’ into the political system and on the ‘output’ in the form of managerial decisions is presented. It is concluded that the qualitative assessment of incoming information affects the quality of managerial decisions that have a significant impact on the lives of citizens. Moreover, it is concluded that by using internal and external information flows, the image of the municipal government is formed, which introduces into the mass consciousness through certain media channels. At the same time, the image of the municipal government is influenced not only by municipal political events, but also by regional and nationwide, which is most notably in the period of the anti-Russian economic sanctions. The article reveals the necessity of combining the domestic experience and current conditions in this field. It is suggested to solve the issue of the possible risks in the field of municipal administration, both in theoretical and practical terms, on the basis of the research; the effective mechanisms of insuring the political system against possible shocks seem to be found there.
Keywords: political conflict, municipal authorities, political discourse, information channel, municipal administration, subjects of political relations, authorities, risks, information comfort, society